THE BANEFUL ADVICE OF AGELAOS (Annual of the Faculty of Philosophy in Skopje, 2020)
In the famed speech delivered during the negotiations in Naupaktos, Agelaosamong other things advises Philip V to turn his attention towards the West and thestruggle between Rome and Carthage. The similarities with the advice that Demetriosof Pharos previously gave the king is a reason to doubt its authenticity. That the adviceis ascribed to an Aitolian should not be taken as an argument in favour of its authenticity,but quite the contrary fits in with Polybios’ generally negative image of the Aitoliansin this period. Although its authenticity can not be proved with certainty, at leastin historical context that may not be too important, for the future actions of Philip Vshow that it had little impact on the decision for concluding the Peace of Naupaktos.
Keywords: POLYBIOS; AGELAOS; DEMETRIOS OF PHAROS; PEACE OF NAUPAKTOS